Respuestas

  • Usuario de Brainly
2013-12-10T05:05:59+01:00
A) y = 4x - x^2 ....donde a= -1 , b= 4

=> x= -b / 2a = - (4) / (2*-1)
=> X = - 4 / -1
=> X = 2
Y = 4(2) - (2)^2
Y = 8 - 4
Y =4
Vértice= (2,4)

b) Y = 3 - x - 3x^2 ... donde a= -3 , b= -1

=> X = -b / 2a = -(-1) / (2*-3)
=> X= 1 / -6

=> X = - (1/6)

Y = 3 - (-1/6) - 3(-1/6)^2

Y = 3 + 1/6 - 1/12
Y = 37/12

Vértice= ( -1/6 , 37/12)

c) Y= 4x^2 + 16x + 4 ...donde a= 4 , b= 16

=> X = -b / 2a = - (16) / (2*4)
=> X = -16 / 8
=> X = - 2

Y = 4(-2)^2 + 16(-2) + 4
Y = 4(4) - 32 + 4
Y = 16 - 32 + 4

Y= -12

Vértice= ( -2,-12)

Nota: le adjunto las gráficas de cada una, adjunto el documento.
saludos.
renedescartes